Early-stage visual processing deficits in schizophrenia - Butler, Pamela D. (2005)
PURPOSE OF REVIEW: While cognitive dysfunction including memory and attentional deficits are well known in schizophrenia, recent work has also shown basic sensory processing deficits. Deficits are particularly prominent in the visual system and may be related to cognitive deficits and outcome. This article reviews studies of early-stage visual processing in schizophrenia published during the past year. These studies reflect the growing interest and importance of sensory processing deficits in schizophrenia. RECENT FINDINGS: The visual system is divided into magnocellular and parvocellular pathways which project to dorsal and ventral visual areas. Recent electrophysiological and behavioral investigations have found preferential magnocellular/dorsal stream dysfunction, with some deficits in parvocellular function as well. These early-stage deficits appear to be related to higher level cognitive, social, and community function. Structural studies of occipital cortex and particularly optic radiations provide anatomical support for early visual processing dysfunction. SUMMARY: These findings highlight the importance of sensory processing deficits, in addition to higher cognitive dysfunction, for understanding the pathophysiology of schizophrenia. Understanding the nature of sensory processing deficits may provide insight into mechanisms of pathology in schizophrenia, such as N-methyl-d-aspartate dysfunction or impaired signal amplification, and could lead to treatment strategies including sensory processing rehabilitation that may improve outcome.